2016
DOI: 10.1261/rna.055939.116
|View full text |Cite
|
Sign up to set email alerts
|

CFIm25 regulates glutaminase alternative terminal exon definition to modulate miR-23 function

Abstract: Alternative polyadenylation (APA) and alternative splicing (AS) provide mRNAs with the means to avoid microRNA repression through selective shortening or differential usage of 3 ′ UTRs. The two glutaminase (GLS) mRNA isoforms, termed KGA and GAC, contain distinct 3 ′ UTRs with the KGA isoform subject to repression by miR-23. We show that depletion of the APA regulator CFIm25 causes a strong shift to the usage of a proximal poly(A) site within the KGA 3 ′ UTR and also alters splicing to favor exclusion of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Non‐small cell lung cancer lines predominantly express the shorter splice variant GAC, and this form is believed to be important for tumorigenesis in this cancer type . We were previously only able to detect the GAC isoform in HeLa cells under normal conditions . However, since KGA is also overexpressed in some tumors, it has also been suggested that the KGA isoform should also be targeted for cancer therapy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non‐small cell lung cancer lines predominantly express the shorter splice variant GAC, and this form is believed to be important for tumorigenesis in this cancer type . We were previously only able to detect the GAC isoform in HeLa cells under normal conditions . However, since KGA is also overexpressed in some tumors, it has also been suggested that the KGA isoform should also be targeted for cancer therapy .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently discovered a novel shorter form of the KGA transcript which shares the same identical exons with the longer KGA isoform but has a truncated 3′‐UTR . The GAC form has no known miRNA binding sites, whereas both the KGA long, and short forms contain a well‐known miR23 binding site making them subject to miRNA regulation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 a), focusing on the analysis of CFI. Our choice of studying CFI in higher detail is based on several considerations: (i) CFI represents one of the hallmarks of metazoan CPA composition, (ii) it affects APA reactions in vitro [28] , [29] , (iii) its molecular structure is well understood in mammals [20] , and (iv) one of its members, CFI25, was shown to be involved in human pathologies including cancer and tumorigenesis [30] . Remarkably, expression patterns of both CFI25 and CFI68 showed a clear tissue-specific pattern with higher levels of expression of the two factors within the developing central nervous system (CNS) of the Drosophila embryo ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Masamha and colleagues described a more complex GLS regulation mechanism involving CFIm25 and ncRNA (6). Depletion of the alternative polyadenylation (APA) regulator CFIm25 was shown to cause a shift toward the usage of a proximal poly(A) site within the KGA 3 0 untranslated region (UTR), which altered splicing to favor the exclusion of the GAC 3 0 UTR.…”
mentioning
confidence: 99%